Linear growth patterns in small for gestational age and preterm infants after zinc supplementation - Caecilia Nancy Setiawan; Gatot Irawan Sarosa; Mexitalia Setiawati (Paediatrica Indonesiana, 2015)
Background Low birth weight (LBW) infants are at risk for growth disturbances due to intrauterine zinc deficiency. Zinc supplementation is expected to improve the linear growth of LBW babies. Objective To assess the effect of zinc supplementation on linear growth in preterm and small for gestational age (SGA) infants. Methods This quasi-experimental study had a pre- and post-test design. Subjects were LBW infants hospitalized in Kariadi Hospital during March-December 2011, consisted of SGA and preterm neonates. All subjects were given 5 mg of zinc syrup daily for 3 months. Subjects’ head circumference, weight, and length were measured monthly. Serum zinc levels were measured before and after supplementation. Data were analyzed with Chi-square test, independent T-test, and general linear model repeated measure. Results A total of 61 subjects were enrolled consisted of 31 preterm and 30 SGA neonates. Mean serum zinc levels in the preterm group were 168.2 (SD 54.5) μg/dL pre-supplementation and 163.6 (SD 50.7) μg/dL post-supplementation (P=0.049), while mean serum zinc levels in the SGA group were 174.8 (SD 46.6) μg/dL pre-supplementation and 167.4 (SD 49.4) μg/dL post-supplementation (P=0.271). Median percentage preterm weight and length increased from 87.3 to 102.4% in the third month (P<0.001) and from 95.8 to 103.9% in the third month (P<0.001), respectively. Median percentage SGA weight and length increased from 73.5 to 98.3% in the third month (P<0.001) and from 94.5 to 102.2% in the third month (P<0.001), respectively. Conclusion Both, the preterm and SGA infants exhibit catch-up growth after three months of zinc supplementation. [